Pengaruh Fraudulent Financial Reporting, Employee Morality, dan Persepsi Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi Yang Dimoderasi Oleh Sistem Pengendalian Internal - Mutiara Puri, Rara; Zanaria, Yulita; Retnaning Rahayu, sri (Universitas Muhammadiyah Metro, 2024)
This research is a type of quantitative research using a comparative causal study that leads to a causal relationship. Data collection was carried out using the questionnaire method and processed using SPSS Statistics 25 with a sample of 30. The results of this study indicate that the fraudulent financial reporting variable has a positive and significant effect on accounting fraud, the employee morality variable has a positive and significant effect on accounting fraud, the compensation suitability variable has a negative effect and significant to accounting fraud, fraudulent financial reporting variable has a positive and significant effect on accounting fraud which is moderated by the internal control system, employee morality variable has a negative and significant effect on accounting fraud which is moderated by the internal control system, compensation suitability variable has a positive and significant effect on fraud accounting moderated by the internal control system, and internal control system variables have a positive and significant effect on accounting fraud.